Meningkatkan Aktivitas dan Hasil Belajar IPA Siswa Kelas V untuk Menanamkan Karakter Peduli Lingkungan Menggunakan Integrasi Model Pembelajaran Problem Based Learning, Talking Stick dan Media Audio Visual di Sekolah Dasar - Sutan Arief Wandhani; Muhsinah Annisa (Jurnal Teknologi Pendidikan Dan Pembelajaran | E-ISSN : 3026-6629, 2023)
This research was aimed at describing teacher activities, analyzing student activities, learning outcomes and describing the environmentally caring character of science content in fifth grade elementary school students using the integration of Problem Based Learning, Talking Stick and audio visual media learning models. Data collection in this research was carried out using the test method which was obtained through individual written tests to measure student learning outcomes and non-test methods obtained through observation of teacher activities and student activities. This type of research is Classroom Action Research (PTK) which is carried out in 2 cycles, where cycle I consists of 2 meetings and cycle II consists of 1 meeting. The subjects of this research were 17 grade V elementary school students in the even semester of the 2022/2023 academic year. The results of this research show that the percentage of student activity initially reached 39% with the criterion "Less Active" in the low category, in cycle II the average percentage of student activity obtained was 82% with the criterion "Very Active." Completeness of student learning outcomes, in the cognitive aspect, shows that in cycle I the percentage of 59% of students achieved completeness, in cycle II the percentage increased to 100%. Affective aspect (character that cares about the environment), in cycle I the percentage reached 53% with the criteria "Not yet visible" in the low category, in cycle II it increased to reach a percentage of 88% with the criterion "Starting to Develop and Become entrenched". The psychomotor aspect in cycle I reached 39% with the criteria "Not Good" in the low category, and in cycle II the percentage reached 82% with the criteria "Good and Very Good". The results of the research show that the implementation of the integration of the Problem Based Learning, Talking Stick and audio-visual media learning models can increase activity, student learning outcomes and the character of caring for the environment in grade V elementary school science content